Transformative Learning Theory and the Missing Focus: How to Enable Perspective Transformation through Communication - Saskia Eschenbacher (Adult Education Research Conference, 2014)
This approach focuses on the question how to challenge the learners’ intrapersonal communication within his/her taken-for-granted worldview through (interpersonal) communication. This means not to focus solely on the question how learning leads to change, but also on how the adult educator is able to initiate and catalyze changes through communication.